Event Sebagai Media Branding Institusi - Putri, Amalia Rosyadi (Institut Agama Islam Syarifuddin Lumajang, 2021)
Promotional activities at a corporate will progress if they have various innovative ideas in promoting products. In this case, not only through advertisements or offers or sponsorships and brochures, but it is necessary to add the latest ideas or breakthroughs in promotion to create a corporate brand. There are many things that companies can do to carry out promotions, one of which is to hold an event with Integrated Marketing Communication to increase pranding in institutions. This paper is an important conceptual framework in analyzing the urgency of envent as an institutional branding medium using the concept of Integrated Marketing Communication theory with management, communication and marketing approaches.Events as institutional branding media can be analyzed pre-designing strategies using three marketing conceptions, namely segmenting, targeting and positioning. The next stage is to understand the pattern of marketing communication strategies at institutions. This pattern is a combination of three disciplines, marketing, communication and strategic management which then results. The final step is the implementation of sponsorship events as a form of integrated marketing communication tools, the implementation of this process is described in a planning framework in achieving the institutional vision.Keywords: Event, Media & Branding